Influence of dietary supplementation of short‐chain fatty acid sodium propionate in people living with HIV (PLHIV). (16th March 2022) - Brauckmann, V.; Nambiar, S.; Potthoff, A.; Höxtermann, S.; Wach, J.; Kayser, A.; Tiemann, C.; Schuppe, A.K.; Brockmeyer, N.H.; Skaletz‐Rorowski, A.
Abstract: Background: Non‐AIDS‐associated chronic diseases in HIV+ patients have been on the rise since the advent of antiretroviral therapy. Especially cardiovascular diseases and disruption in the gastrointestinal tract have limited health‐related quality of life (QoL). Several of those complications have been associated with chronic systemic inflammation. Short‐chain fatty acids (SCFA), with propionate as one of the major compounds, have been described as an important link between gut microbiota and the immune system, defining the pro‐ and the anti‐inflammatory milieu through direct and indirect regulation of T‐cell homeostasis. The effects of dietary supplementation of sodium propionate (SP) in people living with HIV (PLHIV) have not yet been investigated prior to this study. Objectives: To investigate the impact of SP uptake among PLHIV and its relevance to improve QoL, the study aimed to investigate metabolic, immunological, microbiome and patient‐reported QoL‐related changes post‐SP supplementation with follow‐up. Methods: A prospective, non‐randomized, controlled, monocentric interventional study was conducted in WIR, Center for Sexual Health and Medicine, in Bochum, Germany. 32 HIV+ patients with unaltered ART‐regimen in the last three months were included. Participants were given SP for a duration of 12 weeks in the form of daily oral supplementation and were additionally followed‐up for another 12 weeks. Results: The supplementation of SP was well tolerated. We found an improvement in lipid profiles and long‐term blood glucose levels. A decrease in pro‐inflammatory cytokines and a depletion of effector T cells was observed. Regulatory T cells and IL‐10 decreased. Furthermore, changes in taxonomic composition of the microbiome during follow‐up were observed and improvement of items of self‐reported life‐quality assessment. Conclusion: Taken together, the beneficial impact of SP in PLHIV reflects its potential in improving metabolic parameters and modulating pro‐inflammatory immune responses. Thus, possibly reducing the risk of cardiovascular disorders and facilitating long‐term improvement of the gut flora.